Competencies for Evaluation as a Civic Science - Thomas Schwandt (The Evaluation Center at Western Michigan University, 2023)
This paper relocates the practice of evaluation from its traditional intellectual home in the applied social sciences to an interdisciplinary intellectual community that draws on concepts and practices from civic studies, political science, and studies of coproduction and citizen engagement in public administration and management. It offers an overview of the competencies for evaluation practice once relocated in this way.